Could diabetes be a risk factor for penile cancer?: on the subject of a case - Díaz-Meyzan , Lesly (2021)
Penile cancer is rare and most frequently affects older men. We report the case of a male patient with a history of tuberculosis and also suffering from diabetes mellitus (DM), who presented squamous cell penile cancer and underwent satisfactory surgical treatment. The purpose of the article is to show the possible relationship between diabetes and penile cancer, being this an infrequent neoplasm in the area. However, it is advisable to keep it in mind in order to make an early diagnosis and timely treatment.